Factors affecting social integration after road traffic orthopaedic injuries in Rwanda - Allen Ingabire, JC; Stewart, Aimee; Uwakunda, Carine; Mugisha, Didace; Sagahutu, Jean Baptiste; Urimubenshi, Gerard; Tumusiime, David K.; Bucyibaruta, Georges (Frontiers in Rehabilitation Sciences, 2024)
Background:Road traffic injuries (RTIs) leading to long-term disability present a significant public health challenge, causing immense personal and societal consequences.Every year, 50 million people are hurt, 1.2 million die, 30% are permanently disabled, and 14% cannot return to work due to road traffic accidents. However, in many developing countries, information on the social integration of patients post-RTI remains limited. This study aimed to identify factors contributing to social integration following road traffic-related orthopedic injuries (RTOI) in Rwanda.A multicenter, cross-sectional study included 369 adult Road traffic orthopedic injuries (RTOI) victims from five Rwandan referral hospitals. Participants completed the IMPACT-S Questionnaire between June 2, 2022, and August 31, 2022, two years after the injury. It measured social integration in terms of activities and participation. We used logistic regression statistical analysis with a significance level of p<0.05 to estimate odds ratios (OR) and 95% confidence intervals (CI). The Institutional Review Board for Health Sciences and Medicine at the University of Rwanda College of Medicine ethically authorized this study. Participants signed a written consent form before participating in the study. The data was kept private and was used only for this study. The study's findings indicated that the mean age of RTOI victims was 37.5±11.26 years, with a notable male predominance over females. Of the participants, 5.69% were unable to resume normal life activities. The overall mean score on the IMPACT-S scale was moderate, at 77±17. Specifically, participants achieved an average score of 76±16 for "activities" and a higher average of 84±16 for "participation¨.Certain factors were associated with poor social integration compared to others, including belonging to the age group above 65 years (OR=8.25, p=0.02), female sex (OR=3.26, p=0.02), lack of rehabilitation (OR=3.82, p=0.01), and length of hospital stay > 15 days (OR=4.44, p=0.02). The majority of RTOI victims in Rwanda achieved successful reintegration into society; nevertheless, their mobility and community engagement were more significantly impacted compared to other aspects assessed by the IMPACT-S scale.The study emphasized the importance of early management, effective rehabilitation, and prompt patient discharge from the hospital in facilitating a successful return to everyday life after road traffic-related orthopedic injuries.